Self-powered carbon-based photoelectric sensor and preparation method and application thereof

CN122962073APending Publication Date: 2026-10-23KUNMING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510484826.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-17
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0003]当前,POPs常用检测技术主要使用气相色谱仪、质谱分析仪、高效液相色谱仪等一系列大型分析仪器,这些检测技术普遍存在检测手段复杂、分析时间长、成本高、检测仪器体积大以及难以野外在线检测的问题

Benefits of technology

[0020]本发明提供了一种自供电碳基光电传感器的制备方法,包括以下步骤:将蚕丝、弱碱性物质和水混合进行脱胶,得到预处理蚕丝;将所述预处理蚕丝在强碱水溶液中进行炭化后,和氧化型催化剂混合进行水热反应,得到碳基纳米纤维;将所述碳基纳米纤维、粘结剂和溶剂混合,将得到的电极膜液涂覆于基底的导电面,得到自供电电极;以所述自供电电极为工作电极制备自供电碳基光电传感器。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005363831830000011
    Figure HDA0005363831830000011
  • Figure HDA0005363831830000012
    Figure HDA0005363831830000012
  • Figure HDA0005363831830000021
    Figure HDA0005363831830000021
Patent Text Reader

Abstract

The application belongs to the technical field of analysis and detection, and particularly relates to a self-powered carbon-based photoelectric sensor and a preparation method and application thereof. The preparation method comprises the following steps: mixing silk, a weak alkaline substance and water to perform degumming, to obtain pretreated silk; after carbonizing the pretreated silk in a strong alkaline aqueous solution, mixing the pretreated silk with a catalyst to perform a hydrothermal reaction, to obtain carbon-based nanofibers; mixing the carbon-based nanofibers, a binder and a solvent, coating the obtained electrode film liquid on a conductive surface of a substrate, to obtain a self-powered electrode; and using the self-powered electrode as a working electrode to prepare a self-powered carbon-based photoelectric sensor. The application uses silk as a raw material, and prepares flexible and high-conductivity carbon-based nanofibers through a hydrothermal method, and then the carbon-based nanofibers are spin-coated on a conductive optical glass to prepare a self-powered carbon-based photoelectric sensor, which is used for detection of persistent organic pollutants, has high sensitivity, and is simple in equipment and convenient for on-site real-time detection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of analytical detection technology, specifically relating to a self-powered carbon-based photoelectric sensor, its preparation method, and its application. Background Technology

[0002] Persistent organic pollutants (POPs) are characterized by their environmental persistence, bioaccumulation, high toxicity, strong chemical stability, and ability to migrate over long distances, posing a wide-ranging and long-term threat to human health and wildlife.

[0003] Currently, common POPs detection techniques primarily utilize large analytical instruments such as gas chromatographs, mass spectrometers, and high-performance liquid chromatographs. These techniques generally suffer from problems including complex detection methods, long analysis times, high costs, large instrument sizes, and difficulty in online field detection. Furthermore, when analyzing POPs in different environments using these techniques, samples often require a series of complex pretreatments, including dissolution, derivatization, extraction, enrichment, and chromatographic separation, before subsequent analysis. For samples with complex matrices, such as urban sewage, lake wastewater, and soil, the pretreatment process is even more complex. During sample pretreatment, physical or chemical changes may occur, severely interfering with the determination of trace POPs in the sample, making it difficult to meet the practical needs of modern analysis. Therefore, there is an urgent need to develop an instrument with high sensitivity, simple equipment, and convenient for real-time on-site detection. Summary of the Invention

[0004] In view of this, the purpose of this invention is to provide a self-powered carbon-based photoelectric sensor, its preparation method, and its application. The self-powered carbon-based photoelectric sensor of this invention is used for the detection of persistent organic pollutants, exhibiting high sensitivity and requiring simple equipment, facilitating real-time on-site detection.

[0005] This invention provides a method for fabricating a self-powered carbon-based photoelectric sensor, comprising the following steps:

[0006] Silkworm silk, a weakly alkaline substance, and water are mixed and degummed to obtain pretreated silkworm silk.

[0007] The pretreated silk was carbonized in a strong alkaline aqueous solution and then mixed with an oxidizing catalyst for a hydrothermal reaction to obtain carbon-based nanofibers.

[0008] The carbon-based nanofibers, binder, and solvent are mixed, and the resulting electrode film liquid is coated onto the conductive surface of the substrate to obtain a self-powered electrode.

[0009] A self-powered carbon-based photoelectric sensor was fabricated using the self-powered electrode as the working electrode.

[0010] Preferably, the weakly alkaline substance includes an alkali metal carbonate, and the alkali metal carbonate includes sodium carbonate.

[0011] Preferably, the mass ratio of the silk and the weakly alkaline substance is 190-210:1-3.

[0012] Preferably, the degumming temperature is 50–70°C and the time is 50–70 min.

[0013] Preferably, the concentration of the strong alkali aqueous solution is 0.1 to 1 mol / L, and the strong alkali in the strong alkali aqueous solution includes alkali metal hydroxides.

[0014] Preferably, the oxidizing catalyst includes one or more of FeCl2, CoCl2, and FeSO4.

[0015] Preferably, the hydrothermal reaction is carried out at a temperature of 180–240°C for a duration of 12–26 hours.

[0016] Preferably, the binder comprises chitosan, and the mass ratio of the carbon-based nanofibers to the binder is 2-10:5-15.

[0017] The present invention also provides a self-powered carbon-based photoelectric sensor obtained by the preparation method described above, comprising a working electrode, a reference electrode, a counter electrode and an electrolyte, wherein the working electrode is a self-powered electrode and the surface of the self-powered electrode is modified with carbon-based nanofibers.

[0018] The present invention also provides the application of the self-powered carbon-based photoelectric sensor described above in the detection of persistent organic pollutants.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] This invention provides a method for preparing a self-powered carbon-based photoelectric sensor, comprising the following steps: mixing silk, a weakly alkaline substance, and water for degumming to obtain pretreated silk; carbonizing the pretreated silk in a strong alkaline aqueous solution, and then mixing it with an oxidizing catalyst for a hydrothermal reaction to obtain carbon-based nanofibers; mixing the carbon-based nanofibers, a binder, and a solvent, and coating the resulting electrode film liquid onto the conductive surface of a substrate to obtain a self-powered electrode; and preparing a self-powered carbon-based photoelectric sensor using the self-powered electrode as the working electrode.

[0021] This invention uses silk as raw material to prepare carbon-based nanofibers via a hydrothermal method. These nanofibers are then spin-coated onto conductive glass to fabricate a self-powered carbon-based photoelectric sensor. By specifically recognizing changes in optical phenomena resulting from the interaction between the analyte and the acceptor, this sensor can specifically identify persistent organic pollutants (POPs). Photoelectric sensors are characterized by fast analysis speed, simple equipment, and low background signal. This invention utilizes a self-powered carbon-based photoelectric sensor for the detection of POPs, offering high sensitivity and simple equipment, facilitating real-time on-site detection of POPs.

[0022] The carbon-based nanofiber material prepared in this invention possesses a large specific surface area and abundant pore structure, providing more active sites and a larger contact area for the electrode surface. This structure facilitates the contact between target molecules and the electrode surface, thereby improving the sensor's adsorption capacity and reaction efficiency for target molecules, and enhancing signal sensitivity. Simultaneously, the carbon-based nanofiber material prepared in this invention exhibits self-powered capability and can be used as a photoelectric sensor for the detection of persistent organic pollutants, demonstrating a wide strain detection range, currently capable of detecting pollutant concentrations as low as 10⁻⁶. -12 mol / L. Attached Figure Description

[0023] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0024] Figure 1 The DPV diagram for identifying high concentrations (300 μM to 3 μM) of tetracycline using the self-powered carbon fiber sensor in Application Example 1;

[0025] Figure 2 The DPV diagram for identifying low concentrations (300 nM to 3 nM) of tetracycline using the self-powered carbon fiber sensor in Application Example 1;

[0026] Figure 3 The DPV diagram for identifying higher concentrations (100 μM to 1 μM) of chloramphenicol using the self-powered carbon fiber sensor in Application Example 2;

[0027] Figure 4 The DPV diagram for identifying low concentrations (100 nM to 10 pM) of chloramphenicol using the self-powered carbon fiber sensor in Application Example 2;

[0028] Figure 5 Example 2 demonstrates the application of a self-powered carbon fiber sensor to identify the DPV of chloramphenicol (100 nM, 100 pM) under darkness and light conditions;

[0029] Figure 6 The DPV diagrams for identifying high concentrations (1 mM) and relatively high concentrations (100 μM to 1 μM) of chloramphenicol by the self-powered carbon fiber sensor in Comparative Example 1 are shown. Detailed Implementation

[0030] This invention provides a method for fabricating a self-powered carbon-based photoelectric sensor, comprising the following steps:

[0031] Silkworm silk, a weakly alkaline substance, and water are mixed and degummed to obtain pretreated silkworm silk.

[0032] The pretreated silk was carbonized in a strong alkaline aqueous solution and then mixed with an oxidizing catalyst for a hydrothermal reaction to obtain carbon-based nanofibers.

[0033] The carbon-based nanofibers, binder, and solvent are mixed, and the resulting electrode film liquid is coated onto the conductive surface of the substrate to obtain a self-powered electrode.

[0034] A self-powered carbon-based photoelectric sensor was fabricated using the self-powered electrode as the working electrode.

[0035] Unless otherwise specified, all materials and equipment used in this invention are commercially available products in the field.

[0036] This invention involves mixing silkworm silk, a weakly alkaline substance, and water to degumme the silk, thereby obtaining pretreated silkworm silk.

[0037] In this invention, the silk is preferably waste silk, which is a high-protein biomaterial. The resulting carbon-based nanofibers have a high nitrogen content, which can enhance adsorption capacity, improve conductivity, and enhance structural stability, thereby ensuring the reliability of test data.

[0038] In this invention, the weakly alkaline substance preferably comprises an alkali metal carbonate, and the alkali metal carbonate preferably comprises sodium carbonate. Preferably, the weakly alkaline substance is first mixed with water to obtain a weakly alkaline solution, and then silk is added; the concentration of the weakly alkaline solution is preferably 0.01–0.04 mol / L.

[0039] In this invention, the mass ratio of the silk and the weakly alkaline substance is preferably 190-210:1-3, and more preferably 197:1.

[0040] In this invention, the degumming temperature is preferably 50-70°C, more preferably 60°C, and the time is preferably 50-70 min, more preferably 60 min; the degumming is preferably carried out in a constant temperature water bath until the water evaporates completely, so as to remove impurities and moisture from the fiber and make the fiber structure more stable.

[0041] After obtaining the pretreated silk, the present invention carbonizes the pretreated silk in a strong alkaline aqueous solution, and then mixes it with an oxidizing catalyst to carry out a hydrothermal reaction to obtain carbon-based nanofibers.

[0042] In this invention, the concentration of the strong alkali aqueous solution is preferably 0.1 to 1 mol / L, and the strong alkali in the strong alkali aqueous solution preferably includes an alkali metal hydroxide, specifically potassium hydroxide (KOH); the ratio of the strong alkali aqueous solution to silk is preferably 5 to 10 mL: 2 g.

[0043] In this invention, the carbonization is preferably carried out under stirring conditions, and the carbonization time is preferably 4 to 10 minutes.

[0044] In this invention, the oxidizing catalyst preferably includes one or more of FeCl2, CoCl2, and FeSO4, more preferably ferrous chloride tetrahydrate; the catalyst functions to lower the activation energy, provide active sites for adsorption, and catalyze redox reactions and dehydration reactions. The preferred ratio of the catalyst to the strong alkaline aqueous solution is 5-10 mg: 5-10 mL.

[0045] In this invention, the preferred temperature for the hydrothermal reaction is 180–240°C, more preferably 180–200°C, and the preferred time is 12–26 h, more preferably 15–24 h; the hydrothermal reaction is preferably carried out in a vacuum drying oven. During the hydrothermal reaction, the carbonized silk undergoes hydrolysis, depolymerization, dehydration, decarboxylation, and decarbonylation reactions under the action of a catalyst, decomposing into small molecules. Subsequently, these small molecules undergo condensation polymerization to form carbon-based nanofibers.

[0046] In this invention, taking FeCl2 as a catalyst as an example, the hydrothermal reaction yields a mixed carbon-based fiber liquid sample, which includes the product of silk carbonization, iron oxides or hydroxides generated by the reaction of FeCl2 with carbon-based fibers, and a small amount of incompletely removed sericin and impurities.

[0047] In this invention, the hydrothermal reaction preferably further includes: solid-liquid separation of the obtained mixed carbon-based fiber liquid sample, and washing and drying the obtained solid. The solid-liquid separation is preferably performed by centrifugation, with a preferred centrifugation speed of 6000–8000 r / min, a preferred centrifugation time of 8–15 min, and a preferred temperature of 4°C. The washing is preferably performed with water, and the number of water washes is preferably 2–3 times; the drying is preferably freeze-drying.

[0048] After obtaining the carbon-based nanofibers, the present invention mixes the carbon-based nanofibers, binder and solvent, and coats the resulting electrode film liquid onto the conductive surface of the substrate to obtain a self-powered electrode; and prepares a self-powered carbon-based photoelectric sensor using the self-powered electrode as the working electrode.

[0049] In this invention, the binder preferably comprises chitosan or Nafion, and the mass ratio of the carbon-based nanofibers to the binder is preferably 2–10:5–15, more preferably 7:10. The solvent is preferably an aqueous acetic acid solution, the mass concentration of which is preferably 0.1–0.5%, and the ratio of the carbon-based nanofibers, binder, and solvent is preferably 2–10 mg:5–15 mg:1.5 mL. The mixing method is preferably ultrasonic, and the ultrasonication time is preferably 20–60 min.

[0050] In this invention, the substrate preferably comprises conductive glass, conductive plastic, or a transparent conductive film. The coating preferably comprises spin coating, spray coating, or blade coating, and more preferably spin coating.

[0051] In this invention, the conductive optical glass is preferably ITO conductive glass, and after spin-coating the electrode film liquid onto the conductive surface of the conductive optical glass, drying is preferably also included, and the drying is preferably natural drying.

[0052] In this invention, the reference electrode of the self-powered carbon-based photoelectric sensor is preferably silver chloride, the counter electrode is preferably platinum wire, the electrolyte is preferably phosphate buffer, and the pH value of the phosphate buffer is preferably 7-9.

[0053] The present invention also provides a self-powered carbon-based photoelectric sensor obtained by the preparation method described above, comprising a working electrode, a reference electrode, a counter electrode and an electrolyte, wherein the working electrode is a self-powered electrode and the surface of the self-powered electrode is modified with carbon-based nanofibers.

[0054] The present invention also provides the application of the self-powered carbon-based photoelectric sensor described above in the detection of persistent organic pollutants.

[0055] In this invention, the persistent organic pollutant preferably includes tetracycline or chloramphenicol.

[0056] In this invention, the detection of persistent organic pollutants preferably includes the following steps: adding the test solution to the electrolyte and reacting, and then measuring the photocurrent density.

[0057] The reaction time after adding the test solution is preferably 3–5 minutes, with a dark condition used as a control experiment. The reaction mainly includes photoexcitation to generate electron-hole pairs, electron-hole pair separation and transfer, and electrochemical reaction to generate photocurrent, etc. The photocurrent density is measured using an electrochemical workstation.

[0058] This invention utilizes the biocompatibility and flexibility of silk to obtain a highly sensitive and selective self-powered sensor for the determination of persistent organic pollutants. This invention expands the application of silk-based carbon materials by applying them to the working electrode, providing a new approach for the field of photoelectrochemical analysis. The carbon-based nanofibers of this invention self-power under solar radiation to detect organic pollutants ranging from macro to micro levels, and can distinguish between trace and micro levels of organic pollutants, differentiating the types of persistent organic pollutants based on differences in oxidation peak values.

[0059] To further illustrate the present invention, the self-powered carbon-based photoelectric sensor, its preparation method, and its application provided by the present invention will be described in detail below with reference to the accompanying drawings and embodiments, but these should not be construed as limiting the scope of protection of the present invention.

[0060] Example 1

[0061] The method for preparing a self-powered bio-carbon-based photoelectrochemical sensor includes the following steps:

[0062] (1) Treatment of waste silk: Measure 5 mL of sodium carbonate solution with a concentration of 0.02 mol / L into a beaker, add distilled water to make the total volume 70 mL, slowly add 2.0849 g of silk, stir evenly, heat in a water bath at a temperature of 50℃, and react at a constant temperature for 50 min until the water in the solution evaporates completely to obtain pretreated silk.

[0063] (2) The pretreated silk obtained in step (1) is used to prepare carbon-based fibers by hydrothermal method. The specific steps are as follows: 5 mL of 0.1 mol / L KOH solution is added to the pretreated silk sample and reacted for 4 min. Then, 5 mg of FeCl2 is added and placed in a vacuum drying oven at 180℃ for 15 h to obtain a brown mixed carbon-based fiber liquid sample.

[0064] (3) The mixed carbon-based fiber liquid sample was frozen and centrifuged at 6000 r / min and 4℃ for 8 min. The supernatant was removed. A small amount of water was added to the collected coarse sample, and the mixture was centrifuged again. This process was repeated twice to collect the solid particles, freeze them, and dry them to obtain carbon-based nanofibers.

[0065] (4) Preparation of carbon-based nanofiber self-powered electrode: The specific steps are as follows: Mix 2 mg of carbon-based nanofibers, 5 mg of chitosan, and 1500 μL of 0.1% acetic acid solution, and ultrasonically disperse for 20 min to prepare an electrode film solution. Place 20 μL of the electrode film solution on the conductive surface of a conductive glass using a spin-coating method, and allow it to dry naturally for later use.

[0066] (5) A self-powered photoelectrochemical sensor was prepared using a carbon-based nanofiber self-powered electrode as the working electrode, silver chloride as the reference electrode, platinum wire as the counter electrode, and a phosphate buffer solution with a pH of 7.0 as the electrolyte.

[0067] Application Example 1

[0068] The self-powered photoelectrochemical sensor prepared in Example 1 was used to detect tetracycline under sunlight, including the following steps:

[0069] Different concentrations of tetracycline were added to the electrolyte of the self-powered photoelectrochemical sensor. The concentrations of tetracycline in the electrolyte solution after addition were 300 μM, 30 μM, 3 μM and 300 nM, 30 nM, 3 nM, respectively. After reacting for 3 min, photocurrent was measured on a photoelectrochemical measuring instrument, with dark conditions as a control experiment.

[0070] Figure 1 The DPV diagram for identifying high concentrations (300 μM to 3 μM) of tetracycline using the self-powered carbon fiber sensor in Application Example 1; Figure 2 The image shows the DPV (Digital Current Detection) of low concentrations (300 nM to 3 nM) of tetracycline identified by the self-powered carbon fiber sensor in Application Example 1. It can be seen that this carbon-based photoelectric sensor can rapidly identify tetracycline. Within the range of 300 μM to 3 μM, the photocurrent density increases with decreasing tetracycline concentration, and within the same range, it increases with increasing tetracycline concentration. The photoelectric signal initially strengthens (300 μM to 3 μM) and then weakens (300 nM to 3 nM) as the tetracycline concentration decreases. This characteristic enables the self-powered carbon fiber sensor to efficiently detect trace and ultra-trace concentrations of tetracycline, providing it with high sensitivity and a wide dynamic range for application.

[0071] Sensitivity reaches 10 -12 A / V represents the ratio of the change in output signal to the change in input signal, that is, the system's responsiveness to changes in the measured physical quantity. It means that for every 1 volt (V) voltage change applied, the system's output current changes by 10. -12 A. The effective range of the sensor for the concentration of the analyte is 1 mM to 1 pM.

[0072] Application Example 2

[0073] The self-powered photoelectrochemical sensor prepared in Example 1 was used to detect chloramphenicol under sunlight, including the following steps:

[0074] Chloramphenicol at different concentrations (10 pM to 100 μM) was added to the electrolyte of a self-powered photoelectrochemical sensor. After reacting for 3 min, DPV analysis was performed.

[0075] Figure 3 The DPV diagram for identifying higher concentrations (100 μM to 1 μM) of chloramphenicol using the self-powered carbon fiber sensor in Application Example 2; Figure 4 The DPV diagram for identifying low concentrations (100 nM–10 pM) of chloramphenicol using the self-powered carbon fiber sensor in Application Example 2 is shown. It can be seen that this carbon-based photoelectric sensor can rapidly identify chloramphenicol, and there is a significant difference in photocurrent density changes between 100 μM–1 μM and 100 nM–10 pM: in 100 μM–1 μM, the decrease in photocurrent density is smaller and the rate of decrease is slower; in 100 nM–10 pM, the rate of decrease in photocurrent density is faster. This indicates that in the low concentration range, the photocurrent density is more sensitive to concentration changes, and the sensor has a stronger response capability. In the higher concentration range (100 μM–1 μM), the initial value of the photocurrent density is higher and decreases monotonically with decreasing concentration, indicating that the electrochemical reaction is dominated by the active site saturation effect. In the trace concentration range (100 nM to 10 pM), the peak photocurrent density corresponding to each concentration was higher than that of the blank control group, indicating that the self-powered carbon fiber sensor can effectively detect the presence of target substances based on the change in photocurrent peak value. At the same time, the initial value of photocurrent is low and the trend of change is nonlinear, which may be due to the influence of changes in surface adsorption behavior at low concentrations. This difference reflects the change in the response mechanism of the sensor in different concentration ranges.

[0076] Figure 5 The DPV diagrams for identifying chloramphenicol (100 nM, 100 pM) under darkness and light conditions are shown in Example 2. The diagrams demonstrate that the photocurrent density under light conditions is greater than that under darkness conditions. Under light conditions, the sensor is self-powered and requires no external power source.

[0077] Sensitivity reaches 10 -12 A / V. The sensor can effectively operate with a sensitivity of up to 10 for the concentration of the analyte. - 12 mol / L.

[0078] Comparative Example 1

[0079] The difference from Example 1 is that no catalyst (FeCl2) is added in step (2), while the rest of the steps are the same.

[0080] Figure 6To illustrate the DPV (Digital Current Density) of the self-powered carbon fiber sensor in Comparative Example 1 for identifying high concentrations (1 mM) and relatively high concentrations (100 μM–1 μM) of chloramphenicol, DPV analysis was performed at the high concentration of 1 mM chloramphenicol. The photocurrent density values ​​exhibited abnormal fluctuations, indicating that the sensor could not maintain a normal response in the high concentration region (1 mM), limiting its detection range. This may be due to the low porosity and few oxygen-containing functional groups on the surface of the carbon-based nanofibers prepared in Comparative Example 1, leading to saturation of active sites at high concentrations.

[0081] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, not all embodiments. People can obtain other embodiments based on the present invention without creative effort, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for fabricating a self-powered carbon-based photoelectric sensor, characterized in that, Includes the following steps: Silkworm silk, a weakly alkaline substance, and water are mixed and degummed to obtain pretreated silkworm silk. The pretreated silk was carbonized in a strong alkaline aqueous solution and then mixed with an oxidizing catalyst for a hydrothermal reaction to obtain carbon-based nanofibers. The carbon-based nanofibers, binder, and solvent are mixed, and the resulting electrode film liquid is coated onto the conductive surface of the substrate to obtain a self-powered electrode. A self-powered carbon-based photoelectric sensor was fabricated using the self-powered electrode as the working electrode.

2. The preparation method according to claim 1, characterized in that, The weakly alkaline substance includes alkali metal carbonates, and the alkali metal carbonates include sodium carbonate.

3. The preparation method according to claim 1 or 2, characterized in that, The mass ratio of the silk and the weakly alkaline substance is 190–210:1–3. 。 4. The preparation method according to claim 1, characterized in that, The degumming temperature is 50–70°C, and the time is 50–70 minutes.

5. The preparation method according to claim 1, characterized in that, The concentration of the strong alkali aqueous solution is 0.1 to 1 mol / L, and the strong alkali in the strong alkali aqueous solution includes alkali metal hydroxides.

6. The preparation method according to claim 1, characterized in that, The oxidizing catalyst includes one or more of FeCl2, CoCl2, and FeSO4.

7. The preparation method according to claim 1 or 6, characterized in that, The hydrothermal reaction is carried out at a temperature of 180–240°C for a duration of 12–26 hours.

8. The preparation method according to claim 1, characterized in that, The binder includes chitosan, and the mass ratio of the carbon-based nanofibers to the binder is 2-10:5-15.

9. The self-powered carbon-based photoelectric sensor obtained by the preparation method according to any one of claims 1 to 8, characterized in that, It includes a working electrode, a reference electrode, a counter electrode, and an electrolyte. The working electrode is a self-powered electrode, and the surface of the self-powered electrode is modified with carbon-based nanofibers.

10. The application of the self-powered carbon-based photoelectric sensor of claim 9 in the detection of persistent organic pollutants.